Аналіз негативного впливу полігонів твердих побутових відходів на довкілля - Шестопалов, Олексій Валерійович; Сакун, Антоніна Олегівна; Макєєв, Павло Валентинович; Зіньковський, Артем Олександрович (ФОП Яроченко Я. В., 2024)
Descriptions of ground of hard domestic wastes, middle composition of wastes acting on a ground, and description of factions, are resulted in work. The analysis of results of researches is conducted and recommendations are offered on the decline of ecological danger of operating and again appearing grounds.
Keywords: полігони; довкілля; побутові відходи; інженерні споруди; промислові відходи; забруднення навколишнього середовища